Domestication dans les cacaoyères de la zone de forêt humide du Sud-Cameroun: caractéristiques et préférences des cacaoculteurs pratiquant l’arboriculture de Dacryodes edulis - Sanwa, D.J.; Tchatat, M.; Adesina, A.A.; Weise, Stephan F.; Nkongmeneck, B.A.; Ndoye, O.; Endamana, D. (Presses Universitaires d'Afrique, 2002)
The aim of this paper is to determine the characteristics and preferences of cocoa farmers in the humid forest zone of Cameroon who are actively diversifying their cocoa agroforests by planting Dacryodes edulis. A survey conducted amongst 300 farmers revealed that about 80 percent of them grow Dacryodes edulis in cocoa agroforests. More than half of them have completed primary school, half belong to farmer associations and only 10 percent have contact with extension services. This demonstrates the independent initiative of farmers to grow Dacryodes edulis and underlines the importance of capturing their knowledge and experience in integrating this fruit tree into cocoa agroforests. The number of cocoa agroforests per farmer decreases as one moves from a more forested area to one where pressure on land is greater. Dacryodes edulis is frequently associated with other planted fruit trees. However, in areas of higher land pressure it is often also planted together with other tree species. Overall, 47 percent of farmers plant at least 4 fruit trees and 38 percent at least 4 other tree species in their cocoa agroforests besides Dacryodes edulis. The interest in Dacryodes edulis does not prevent farmers from diversifying their tree stock within the cocoa agroforests. Dacryodes edulis complements other trees in addressing the need of farmers.